Cu-modified Pb(Mg1/3Nb2/3)O3-PbZrO3-PbTiO3 textured ceramics with enhanced electromechanical properties and improved thermal stability. Issue 6 (June 2022) - Liu, Linjing; Yang, Bin; Yang, Shuai; Kou, Qiangwei; Xie, Hang; Sun, Yuan; Chang, Yunfei; Zhang, Shan-Tao; Li, Fei
Abstract: Grain-oriented Pb(Mg1/3 Nb2/3 )O3 -PbZrO3 -PbTiO3 (PMN-PZ-PT) based ceramics were synthesized through templated grain growth via using BaTiO3 (BT) templates. Although BT templates are partially destroyed by PMN-PZ-PT matrix, CuO addition remarkably promotes [001]c -oriented grain growth behavior of the ceramics, resulting in an improvement of Lotgering factor F 001 from ~86% to 98%. Both crystallographic texture and CuO doping increase tetragonality and reduce average domain size of the ceramics dominated by rhombohedral phase. Consequently, 0.50 wt% CuO-doped ceramics ( F 001 ~98%) exhibit optimum electromechanical properties: d 33 ~860 pC/N, d 33 × g 33 ~48.6 × 10 −12 m 2 /N, k p ~0.80, E c ~7.2 kV/cm, tan δ ~0.8% and T c ~222 °C. In addition to ~3.7 times and 6.6 times higher d 33 and d 33 × g 33, those ceramics possess about 240% enhanced piezoelectric strain and much better thermal stability ( S max / E max variation ≤2% between RT and 150 °C) relative to non-textured counterpart. This work offers a good paradigm for simultaneously exploring high piezoelectric response and good temperature stability in piezoceramics, benefiting the development of next-generation advanced electromechanical devices.